2008
DOI: 10.5737/1181912x183141145
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: The patient’s perspective

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 6 publications
4
27
0
Order By: Relevance
“…[1112] Information has been cited as a critical need by individuals at all points of the cancer journey. [4613] The evidence supports the idea that most, although not all, cancer patients want to be fully informed and receive as much information as possible.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…[1112] Information has been cited as a critical need by individuals at all points of the cancer journey. [4613] The evidence supports the idea that most, although not all, cancer patients want to be fully informed and receive as much information as possible.…”
Section: Introductionmentioning
confidence: 69%
“…[1] Individuals who have been diagnosed with this disease have indicated the importance of information, effective communication, and emotional support in helping them cope with these consequences. [23456] Given its importance, the provision of relevant, understandable information is considered a dimension of quality cancer care. [78]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for these patients, the added mystery and unknown nature of this cancer added to the stigma. In a study by Vlossak and Fitch (2008) most patients had never heard of myeloma before diagnosis. Moreover, less than 3% of the UK population have heard of myeloma (Myeloma UK 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Dahan and Auerbach's (2006) grounded theory study explored the emotional effect of multiple myeloma among patients treated with peripheral blood stem cell transplant at a New York City cancer treatment centre. In addition, Vlossak and Fitch's (2008) qualitative study reported on in-depth telephone interviews with 20 patients receiving treatment for myeloma in a large regional cancer centre in Ontario, Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are some qualitative studies looking at the experience of myeloma from the patient’s perspective. These have explored lived experience [25-28], trauma and post-traumatic growth [29] and distress [30], but there is a paucity of qualitative research to directly characterise the meaning of QOL in this group [13]. …”
Section: Introductionmentioning
confidence: 99%